2016
DOI: 10.1161/hypertensionaha.116.07666
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Stimulation Facilitates Sarcoplasmic Reticulum Ca Release by Modulating Ryanodine Receptor 2 Phosphorylation Through Protein Kinase G and Ca/Calmodulin-Dependent Protein Kinase II

Abstract: While the effects and the underlying mechanism of sympathetic stimulation on cardiac Ca handling are relatively well established both in health and disease, the modes of action and mechanisms of parasympathetic modulation are poorly defined. Here we demonstrate that parasympathetic stimulation initiates a novel mode of excitation-contraction (EC) coupling that enhances the efficiency of cardiac SR Ca store utilization. This “efficient” mode of EC coupling involves reciprocal changes in the phosphorylation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 72 publications
(87 reference statements)
1
26
0
Order By: Relevance
“…For calcium waves to occur a mechanism is required to maintain SR calcium content above threshold (Venetucci et al, 2007 ; Ho et al, 2016 ). SERCA function increases in paroxysmal AF (Xie et al, 2012 ; Voigt et al, 2014 ) which would explain how SR calcium content could be maintained in spite of an increase in RyR mediated calcium leak.…”
Section: The Pathophysiology Of Atrial Fibrillationmentioning
confidence: 99%
“…For calcium waves to occur a mechanism is required to maintain SR calcium content above threshold (Venetucci et al, 2007 ; Ho et al, 2016 ). SERCA function increases in paroxysmal AF (Xie et al, 2012 ; Voigt et al, 2014 ) which would explain how SR calcium content could be maintained in spite of an increase in RyR mediated calcium leak.…”
Section: The Pathophysiology Of Atrial Fibrillationmentioning
confidence: 99%
“…It is well described that short-term β-adrenergic stimulation increases glucose uptake and oxidation (Morisco et al, 2005 ; Nagoshi et al, 2011 ). Stimulation by the use of an agonist (epinephrine) can also favor Ca 2+ handling cycle, with potential beneficial in myocardial contractility (Collins-Nakai et al, 1994 ; Briston et al, 2014 ; Grimm et al, 2015 ; Ho et al, 2016 ). Moreover, recent study demonstrated that a selective β3-adrenergic receptor agonist (BRL 37344 ) favors left ventricular relaxation in Langendorff-perfused rat hearts via the NO/cGMP/PKG axis, thus by activating specific redox signaling and favoring beneficial adaptive process (Angelone et al, 2008 ; Cannavo and Koch, 2017 ).…”
Section: Discussion: Therapeutic Strategiesmentioning
confidence: 99%
“…This effect would counteract the negative inotropic action of HS, which would have been greater in the absence of RyR2 phosphorylation. Supporting this concept, Ho et al (13) recently demonstrated that cholinergic stimulation of the heart produced an increase in SR Ca 2ϩ release at low SR Ca 2ϩ content compared with nonstimulated hearts. The consequent enhancement of FCaR, which occurs without alterations of I Ca , is due to a facilitation of SR Ca 2ϩ release produced by PKG-dependent phosphorylation of RyR2 at the Ser 2808 site.…”
Section: New and Noteworthy Increasing Ryanodine Receptor (Ryr)2mentioning
confidence: 93%